1998
DOI: 10.1126/science.281.5374.257
|View full text |Cite
|
Sign up to set email alerts
|

A Small, Nonpeptidyl Mimic of Granulocyte-Colony- Stimulating Factor

Abstract: A nonpeptidyl small molecule SB 247464, capable of activating granulocyte-colony-stimulating factor (G-CSF) signal transduction pathways, was identified in a high-throughput assay in cultured cells. Like G-CSF, SB 247464 induced tyrosine phosphorylation of multiple signaling proteins and stimulated primary murine bone marrow cells to form granulocytic colonies in vitro. It also elevated peripheral blood neutrophil counts in mice. The extracellular domain of the murine G-CSF receptor was required for the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 22 publications
3
141
0
2
Order By: Relevance
“…Validation experiments run in high throughput format showed that this assay has a stable baseline and can detect compounds with e cacies as low as 10% that of G-CSF. This cell line was used to screen *110 000 individual compounds, and a single compound that triggered an increase in luciferase activity was studied further (Tian et al, 1998). This compound, termed SB 247464, has a molecular weight of 526 and is symmetrical in structure (Figure 4).…”
Section: Cell-based Assaysmentioning
confidence: 99%
“…Validation experiments run in high throughput format showed that this assay has a stable baseline and can detect compounds with e cacies as low as 10% that of G-CSF. This cell line was used to screen *110 000 individual compounds, and a single compound that triggered an increase in luciferase activity was studied further (Tian et al, 1998). This compound, termed SB 247464, has a molecular weight of 526 and is symmetrical in structure (Figure 4).…”
Section: Cell-based Assaysmentioning
confidence: 99%
“…Luciferase Assay-Cytokine-independent NFS60 cells containing a stably integrated STAT-responsive luciferase reporter gene that is induced by G-CSF have been described previously (23). The cells were grown in RPMI containing 10% FBS and split to a density of 2 ϫ 10 5 /ml 2 days before the assay.…”
Section: Methodsmentioning
confidence: 99%
“…Transient Transfection Assays-The human and mouse G-CSF receptor expression constructs have been described previously (23). The chimeric receptors encode the following amino acids: M/H1, mouse amino acids 1-612, human amino acids 612-707; M/H2, mouse amino acids 1-601, human amino acids 601-707; M/H3, mouse amino acids 1-594, human amino acids 592-707.…”
Section: With Either a Single Homogeneous Species Model (Equation 1)mentioning
confidence: 99%
See 2 more Smart Citations